Microstructure crystalline domains disorder critically controls formation of nano-porous/long fibrillar morphology of ePTFE membranes. (14th July 2017) - Ranjbarzadeh-Dibazar, Arash; Barzin, Jalal; Shokrollahi, Parvin
Abstract: Expanded PTFE (ePTFE) membranes were prepared through thermo-mechanical stretching. Thermal modification was performed to take control over morphology of fibrillated structure of ePTFE and membranes with fibril length varying between 50 nm and 52 μm were obtained. SEM observation showed that adequately controlling thermal modification condition results in a wide variety of morphologies. Crystal changes in PTFE were monitored via DSC and XRD which subsequently correlated to the final structures. PTFE crystals show two different linear and folded domains. SEM, DSC and XRD data together indicate that the folded crystalline domains are responsible for fibril length increment under stretching. Effect of lubricant presence on melting points/enthalpies was evaluated by DSC and XRD in order to monitor interrelation between morphology and crystal disorder. Shrinkage evaluation revealed that thermal modification brings about significant decrement of shrinkage. Water entry pressure (WEP) measurements confirmed validity of this approach to fabrication of membranes with adjustable WEP in broad range of 17–624 kp.mm −1 . Graphical abstract: Highlights: Crystal disorder is responsible for formation of different morphologies. Microstructure of crystalline domains play a rule in pore characteristics. Heat treatment induces different morphologies from nano-pores to long fibrils. Zero shrinkage and high porosity are obtained by thermal modification. Oils are utilized as adequate lubricants for ePTFE membrane preparation.